Penerapan Role Playing Investigatif dalam Pembelajaran Teks Rekon di Sekolah Menengah Pertama - Theodelind Eunike Pramesti Dawa Putri; Herlina Herlina (Fakultas Sastra, Universitas Muslim Indonesia, 2026)
Learning recount texts at the junior high school level requires students to reconstruct events in a factual and chronological manner. However, in practice, many students still experience difficulties in organizing event sequences, distinguishing facts from opinions, and maintaining textual coherence. This study aims to describe the implementation of investigative role playing as a learning medium in recount text instruction, students’ responses and learning motivation, and students’ understanding of recount texts. This research employed a descriptive qualitative approach involving a Bahasa Indonesia teacher and ninth-grade students of SMP Katolik Kuala Dua as research subjects. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The results show that investigative role playing was implemented through case investigation activities, code-solving tasks, group discussions, and the construction of recount texts in a chronological order. Students’ responses and learning motivation during the learning process were generally positive, indicated by active participation, curiosity, and collaborative work. In addition, students’ understanding of recount texts was reflected in their ability to construct complete text structures and organize events coherently, although some difficulties in linguistic aspects were still found. This study suggests that investigative role playing can be used as an alternative creative learning strategy in recount text instruction.